PARENTING EARLY AGE BOARDING SCHOOL CHILDREN: CHALLENGES FOR PARENTS - Mbogo, Rosemary Wahu (Advances in Social Sciences Research Journal, 2018)
Biblically, parents are children’s trainers until such a time when the child is adequately grown to take care of themselves. Since parenting is training, it cannot be done effectively with either party being away from the other. Placing children in boarding schools, some at a very early age however breaches this and exposes children to other influencers than their parents. While these influences form their personalities, the question of whether they are well nurtured remains. This paper identifies the challenges that parents face in parenting early age boarding school children. The study used a qualitative design approach. Data was collected using interview with parents, who by then, had their children in boarding school, and those whose children had already gone through boarding schools. A population 200 was targeted in all the four churches. A sample of five (5) parents was purposefully selected from the four churches. The study found out that indeed, parenting boarding scholars is different from parenting day scholars. It also revealed that children in boarding schools exhibited some change in behaviour both negatively and positively. On disadvantages attached to boarding schooling for early age children, this paper revealed that parents risk their children in boarding school to poor feeding, poor medical attention, irresponsible care takers and bullying by older children. The authors concluded that parenting a child in boarding school is challenging. This paper thus recommends ways to improve parent-child relationship.